Micro to Macro: Optimal Trade Policy With Firm Heterogeneity - Costinot, Arnaud; Rodríguez-Clare, Andrés; Werning, Iván (Econometrica, 2020)
The empirical observation that “large firms tend to export, whereas small firms do not” has transformed the way economists think about the determinants of international trade. Yet, it has had surprisingly little impact on how economists think about trade policy. Under very general conditions, we show that from the point of view of a country that unilaterally imposes trade taxes to maximize domestic welfare, the self‐selection of heterogeneous firms into exports calls for import subsidies on the least profitable foreign firms. In contrast, our analysis does not provide any rationale for export subsidies or taxes on the least profitable domestic firms.